INTERPRETATION AND SIGNIFICANCE OF ANAEROBIC THRESHOLD IN BALL GAMES - Fülöp, Tibor (Sport- és Egészségtudományi füzetek, 2025)
Fatigue is a normal result of exertion, although its severity and symptoms vary. Exhaustion increases the likelihood of movement coordination abnormalities, as well as the rate of technical execution errors. As a result of impaired concen-tration and decreased physical performance, the frequency of tactical errors increases. Technical and tactical failures by players destroy collaboration and harmony, causing team play to disintegrate. The inevitable result of this is inaccura-cy in both defense and offense, which, combined with an in-crease in the number of baskets received and a decrease in scoring opportunities, leads to loss. Incorrect movement ex-ecution and overloading significantly raise the risk of injury. The team is made up of individuals. In their case, the devel-opment of endurance can be an important part of preven-tion, which means two things: on one hand, improved endur-ance and on the other hand, rapid regeneration.